2003
DOI: 10.1051/rnd:2003009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of overfeeding on myofibre characteristics and metabolical traits of the breast muscle in Muscovy ducks (Caïrina moschata)

Abstract: -The aim of this experiment was to study the consequences of precise feeding on the myofibre characteristics and metabolic traits of the breast muscle (Pectoralis major, Pm) of Muscovy ducks. Twenty-four samples of breast muscle, without skin or subcutaneous fat, from two groups of ducks, control and overfed respectively, were collected at 14 weeks of age. We assayed different chemical (water content, crude proteins, total lipid ashes, total and thermosoluble collagen), biochemical (activities of the CS, LDH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
4
12
0
Order By: Relevance
“…We observed a large increase in the relative surface occupied by adipocytes on muscle sections: 1.5 fold in P. major and 2.1 fold in Sartorius across genotypes. This confirmed the previous observations of Zanusso et al [20] obtained in Muscovy ducks. The availability of data across a wide range of muscle lipid concentrations in P. major allowed obtaining high correlations between the relative surface occupied by adipocytes in muscle sections and the total lipid (g per Figure 2.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed a large increase in the relative surface occupied by adipocytes on muscle sections: 1.5 fold in P. major and 2.1 fold in Sartorius across genotypes. This confirmed the previous observations of Zanusso et al [20] obtained in Muscovy ducks. The availability of data across a wide range of muscle lipid concentrations in P. major allowed obtaining high correlations between the relative surface occupied by adipocytes in muscle sections and the total lipid (g per Figure 2.…”
Section: Discussionsupporting
confidence: 93%
“…In P. major muscle, overfeeding had no significant effect on the total lipid content of muscle fibres (luminance of Sudan black B staining). Zanusso et al [20] with the same staining procedure also found no significant difference of luminance between control and overfed Muscovy ducks. Inside the fibres, the proportion of phospholipids is Figure 3.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Generally speaking, the muscle tissues adapt their energy metabolism to overfeeding, increasing their oxidative metabolism, and decreasing their glycolytic metabolism, particularly in breast muscle (Zanusso et al, 2003;Chartrin et al, 2006). It has been hypothesised that muscle tissues adapt their metabolism to use more fat as the energy source following overfeeding due to greater fat availability (as demonstrated by higher TG levels in the plasma) and reduce their utilisation of glucose (Chartrin et al, 2006).…”
Section: Hepatic Metabolismmentioning
confidence: 99%